2014
DOI: 10.5198/jtlu.v7i1.373
|View full text |Cite
|
Sign up to set email alerts
|

The influence of transport infrastructures on land-use conversion decisions within municipal plans

Abstract: Transit-oriented development (TOD) is one of the most popular means of public intervention in the field of spatial planning, which aims at reducing land consumption caused by urban sprawl. In this paper, a logit model is computed to assess whether the Municipal Master Plans approved during the 1990s in the Lisbon region (Portugal), currently in force, contemplated public transit stations as a relevant requirement for the location of the planned urban expansion areas and, more specifically, for the conversion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
1
1
0
3
Order By: Relevance
“…Our findings aligned with previous studies that emphasized the highly significant and positive influence of population density on land take (Martinuzzi et al, 2007;Behnisch et al, 2016). Contrary to numerous studies that assumed a causal relation between proximity to central train stations and urban growth or land conversion (Padeiro, 2014), our study found no significant effect of distance on the amount of built-up area. However, our OLS model revealed a significant influence between the proximity to the nearest highway exit and the built area.…”
Section: Discussionsupporting
confidence: 90%
“…Our findings aligned with previous studies that emphasized the highly significant and positive influence of population density on land take (Martinuzzi et al, 2007;Behnisch et al, 2016). Contrary to numerous studies that assumed a causal relation between proximity to central train stations and urban growth or land conversion (Padeiro, 2014), our study found no significant effect of distance on the amount of built-up area. However, our OLS model revealed a significant influence between the proximity to the nearest highway exit and the built area.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have discussed the relationship between land use and transit ridership (e.g., Ewing & Cervero, 2010;Kuby, Barranda, & Upchurch, 2004;Sohn & Shim, 2010;Padeiro, 2014;Tsai & Mulley, 2012;Zhao et al, 2014). These studies underlie the interdependent nature between land use and transit systems through which each supports and shapes the other.…”
Section: Literature Reviewmentioning
confidence: 99%
“…De facto, a localização de novas áreas de urbanização em volta das cidades, analisada, quer através da artificialização dos solos (Bell et al, 2002;abrantes et al, 2013;Padeiro, 2014), quer pelas transacções, licenças de construção ou construção efectiva (Hansen et al, 1998;ewing, 2008), remete para um conjunto de factores determinantes, que podem actuar em diversos sentidos de acordo com o contexto l ocal. Do ponto de vista teórico, o custo dos transportes é o factor de locali zação mais fundamental, encontrando-se na convergência de todas as teorias da localização (glaeser et al, 2004;McCann et al, 2004) e acentuando a probabilidade de urbanização nas áreas servidas por redes novas.…”
Section: Factores Da Conversão De Solos E Da Edificaçãounclassified